Theoretical Study of External Electric Field Effect on the Chemisorption of a Spherical Semiconducting Quantum-dot on Graphene - Fadel, Haider; Abd-AlHussien , Marwa (University of Thi-Qar Journal of Science, 2024)
In This study, we modified the Anderson-Newns model for atomic chemisorption to be suitable for the chemisorption of a spherical semiconducting quantum-dot on a monolayer pure perfect graphene.A mathematical expression was used to calculate the occupation numbers for the two levels of the quantum-dot as a function of the normal distance and the external electric field. Appropriate formulas for other chemisorption functions were  used by taking into our account the effect of image shift, and a formula for hybridization energy as a function of distance only. The quantum-dot was considered a spherical  shape, chooses the type of on-top adsorption on the graphene layer, also taken a fixed value for the correlation energy U to be spin independent and not dependent on distance.At room temperature T=300 K, the occupation numbers and their corresponding energy levels were calculated by stabilizing all the parameters  and varying the strength of electric field individually by both positive and negative directions. The contribution of the negative electric field was more effective on quantum-dot chemisorbed on graphene.